Antibacterial Activity of Robusta Instant Coffee Powder Against Acidogenic and Aciduric Species of Streptococcus mutans Bacteria - Lestari, Pujiana Endah; Susilawati, I Dewa Ayu; Harmono, Happy; Dewanti, I Dewa Ayu Ratna; Masari, Al; Nailufar, Khanun; Morauli, Fatricia (BIOEDUKASI, 2024)
Streptococcus mutans is a major species that causes dental caries due to its acidogenic and aciduric properties. Coffee beans contain several compounds, such as caffeine, phenols, tannins, trigonelline, chlorogenic acid, and caffeic acid, which are known for their antibacterial properties. Robusta instant coffee powder is a stable product that is not easily contaminated with bacteria, fungi, and yeast. It is a zero-waste and soluble material. This study aimed to analyze the antibacterial activity of robusta instant coffee powder (RICP) against S. mutans. The antibacterial activity of RICP against S. mutans was tested using three antimicrobial susceptibility tests: 1) disk diffusion method, 2) minimum inhibitory concentrations (MIC), and 3) minimum bactericidal concentration (MBC). The results of the disk diffusion method test showed that the RICP concentration of 0.2 g/mL to 0.8 g/mL against S. mutans had an inhibition zone of 31.14 mm to 42.01 mm. MIC and MBC values of RICP against S. mutans were both 0.0313 g/mL. In conclusion, robusta instant coffee powder (RICP) demonstrates antibacterial activity against the acidogenic and aciduric S. mutans bacteria.